Origin of Surface Coating Effect for MgO on LiCoO2 to Improve the Interfacial Reaction between Electrode and Electrolyte. Issue 9 (28th August 2014) - Orikasa, Yuki; Takamatsu, Daiko; Yamamoto, Kentaro; Koyama, Yukinori; Mori, Shinichiro; Masese, Titus; Mori, Takuya; Minato, Taketoshi; Tanida, Hajime; Uruga, Tomoya; Ogumi, Zempachi; Uchimoto, Yoshiharu
<x xml:space="preserve">Abstract</x> Surface coating on lithium‐ion battery cathodes improves their durability at high potentials, which is a well‐known practical application. However, the mechanism is still unclear because the coating influences the electrode/electrolyte interface at a few nanometer‐scale and direct observation of the interface under real operating conditions of a battery is challenging. This study reveals the mechanism of the surface coating effect on lithium‐ion battery cathodes by using in operando X‐ray absorption spectroscopy (XAS) on well‐defined MgO‐coated LiCoO2 thin‐film electrodes prepared via pulsed laser deposition. Total‐reflection in operando XAS measurements reveal that LiCoO2 forms a reductive phase at the interface between the uncoated‐LiCoO2 electrode and the electrolyte, while the MgO coating layer inhibits the redox process, leading to an improvement in the cycle performance of the battery. Depth‐resolved in operando XAS measurements indicate that a solid solution of the magnesium phase forms at the LiCoO2 surface upon MgO coating. Magnesium ions function as pillars to stabilize the layered structure at the interface between the LiCoO2 electrode and the electrolyte for delithiated states upon cycling at potentials.